Синантропізація флори Волинської області - Коцун, Лариса Олександрівна; Кузьмішина, Ірина Іванівна; Kotsun, Larysa O.; Kuzmishyna, Iryna I. (My University, 2016)
У складі флори Волинської області виділено 507 синантропних видів, що складає 38,9% від загальної кількості видів. Встановлено переважання апофітів – 287 видів, серед яких за ступенем адаптації до антропогенно порушених умов більшість геміапофітів (149 видів). З’ясовано, що серед антропофітів за часом занесення переважають кенофіти (111 видів), за способом занесення – ксенофіти (111 видів), за ступенем натуралізації – епекофіти (159 видів). Виділено групу адвентивних видів з високою фітоценотичною активністю.

Volyn region is located in northwestern Ukraine. Its territory is plain in the north and poorly hilly in the south with a total obliquely in a northerly direction. The climate is temperate continental with mild winters and moderately warm enough wet summer. Sod-podzolic and meadow soils is predominate, sod, forest-steppe podzolized soils, typical black less common. According to physical and geographic zone, the area belongs to the zone of mixed coniferous-deciduous forests; by geobotanical zoning of Ukraine – the European broadleaved forest region, East European and Central provinces. 1272 species of vascular plants of natural flora grow at the Volyn region which was received as a result of years during the 1999-2015 field surveys and supplemented with materials of literature and herbarium collections. Among them the synanthropic group was isolated, which includes 507 species and representive over 38% of all species. Local synanthropic species is dominated – apophytes (287 species) over antropophytes (220 species). The correlation between these two groups is 1,3:1. This is evidence that synanthropic flora was formed under the influence of native flora and now apophytyzation’s processes is dominated over the adventyzation’s processes. Species with active dissemination strategy in seminatural and transformed ecosystems – hemiapophytes (149 species) – are dominated for the degree of adaptation to anthropogenically disturbed conditions among the apophytes. It was found that 220 species belong to antropophytes among which kenophytes (111 species) dominate by time of entry. There are 109 species of arheophytes. The relationship between these two groups is 0,9: 1,0, which indicates about the moderate process of penetration of alien species to the study area. The ksenophytes (111 species) – species that man unconsciously has bring – dominate by the method of entry. The epekophytes (159 species) – species that occupy a strong position at anthropogenic habitats – dominate to the degree of naturalization. Group of alien species with high phytocoenotic activity is allocated. The herbaceous annuals or milticarpos whith the core root system, without underground shoots, from North American origin, are belonging to this group. They can significantly change their structure, can enter into natural and semi-natural phytocoenoses, can detect invasions.
Flora synanthropization in Volyn region (Ukraine)
Keywords: синантропізація; флора; Волинська область; адвентивні види; synanthropization; flora; Volyn region; alien species